Prediction of lifetime milk production in synthetic crossbred cattle strain Vrindavani of North India - KHAN, T A; TOMAR, A K S; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2012)
Ten-year data records on growth (birth weight-BWt), five initially reproductive traits (age at first calving-AFC, first dry period-FSP, first dry period-FDP, first calving interval-FCI and first lactation length-FLL) along with the part lactation records of 100, 170 and 240days of first lactation (my100_1, my170_1 and my240_1) and second lactation (my100_2, my170_2 and my240_2) and their respective total milk yields (total lactation milk yield of first lactation- TLMY1 and total lactation milk yield of second lactation-TLMY2) were used to predict LTMY5 (lifetime milk yield as total milk yield up to 5 lactations) and LTMY4 (lifetime milk yield as total milk yield up to 4 lactations). It was observed that first calving interval (FCI) happens to be important predictor (out of initially expressed growth – birth weight(BWt), reproductive traits- AFC, FSP, FDP, FCI, FLL and first lactation milk traits- my100_1, my170_1, my240_1 and TLMY1) for lifetime prediction (both LTMY4 and LTMY5). Prediction of LTMY4 and LTMY5 with respect to initial growth (birth weight), reproductive traits (AFC, FSP, FDP, FCI, FLL) and first 2 lactations (my100_1, my170_1 my240_1, TLMY1, my100_2, my170_2 my240_2 and TLMY2) indicated the contribution of my240_2 followed by TLMY1 and my170_2. They jointly explained 40.32% variation in estimated value of LTMY4. However, prediction of LTMY5, with respect to these predictors showed my240_2 together with FLL jointly explained 26.71% variation in estimated value.